Research Notes. Learning from Shabolovka - Алексей Викторович Новиков; Марина Сапунова; Тео Дойтингер; Эрик Викс; Марина Салимгареева; Екатерина Зарудная; Эрнестс Швейсбергс; Аксел Бурвалл; Дэниэл Роч; Лариса Королева; Иннокентий Волянский; Дмитрий Панов; et al. (Городские исследования и практики, 2017)
Urbanism is about research, experimentation, and dialogue. It is the art of posing the right questions about the urban environment, and the science of making the tools to discover relevant answers. The mindset underpinning practical urbanism is no longer dominated by intentions, professional intuition, and visionary concepts alone: Prior to the actual design and planning work, urban designers must now conduct thorough contextual research and intensive quests for analytical insights. These developments in the field of urbanism provide a fundamental basis for the two-year Advanced Urban Design Master’s program, developed by the Higher School of Economics Graduate School of Urbanism and the Strelka Institute. For this reason, Anastasia Smirnova, the academic supervisor of our program, and Theo Doitinger, founder of TD Architects, created the “Learning from Shabolovka” workshop. It focused on contextual analyses of Shabolovka Street in central Moscow, the hub of one of HSE’s busiest campuses.The structure of this four-week workshop had several focuses: conceptualizing and posing inquiry questions, field research, data creation/collection, and finally, the presentation of its findings. Intensive field research of Shabolovka Street was essential for the workshop, as it was the main source of overall research data. Surveys and analyses of doors facing the street, the density of outdoor and indoor lighting, and the ways that coffee-to-go is purchased on the street represent new types of urban data and “urban devices” of a high explanatory power. The collection of this data alone, even without the subsequent research, represents the extraordinary value added by this group of workshop participants. The abstracts below summarize the workshop’s main findings by six groups of bright and talented students, each with its own research story and amazing results. Read and enjoy.